2019
DOI: 10.1002/ajpa.23942
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate and phylogeny on quadrupedal gait in free‐ranging platyrrhines

Abstract: Objectives: Primate diagonal sequence (DS) gaits are often argued to be an adaptation for moving and foraging in the fine-branch niche; however, existing data have come predominantly from laboratory studies that are limited in taxonomic breadth and fail to account for the structural and ecological variation of natural substrates.We test the extent to which substrate diameter and orientation influence gait sequence type and limb phase in free-ranging primates, as well as how phylogenetic relatedness might condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
(129 reference statements)
0
10
0
Order By: Relevance
“…The increased affordability and durability of high-speed cameras and remote sensors now allow researchers to record animals moving in their natural habitats, which ultimately provides more relevant tests of locomotor adaptation (Dunham et al, 2018(Dunham et al, , 2019aMcNamara et al, 2019). Even though the small body sizes characteristic of callitrichines are the result of phyletic dwarfism rather than a retention of a primitive ancestral state (Montgomery and Mundy, 2013), extant callitrichines represent valuable biomechanical analogs for early stages of primate evolution because of their small body size and reduced grasping ability (Nyakatura, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The increased affordability and durability of high-speed cameras and remote sensors now allow researchers to record animals moving in their natural habitats, which ultimately provides more relevant tests of locomotor adaptation (Dunham et al, 2018(Dunham et al, , 2019aMcNamara et al, 2019). Even though the small body sizes characteristic of callitrichines are the result of phyletic dwarfism rather than a retention of a primitive ancestral state (Montgomery and Mundy, 2013), extant callitrichines represent valuable biomechanical analogs for early stages of primate evolution because of their small body size and reduced grasping ability (Nyakatura, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…values ranging from −1 to 1) to test for substrate angles ranging from −90 to 90 deg, thus differentiating declines versus inclines, and (2) cosine of substrate orientation angle (i.e. values ranging from 0 to 1 and back to 0) for substrate angles ranging from −90 deg to 0 deg to 90 deg, thus differentiating oblique supports from horizontal supports, but ignoring the distinction between declines and inclines (Dunham et al, 2019a). Though the resulting transformations of substrate angles were not normally distributed themselves, residual error was normally distributed (in all but two of our models), a condition necessary to satisfy the assumptions of linear mixed-effects regression (Harrison et al, 2018).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…To extend our argument, we require extensive data on the gaits of other quadrupeds on discontinuous supports. By filming the gaits of 11 species of free‐ranging platyrrhine primates, Dunham et al (2019) investigated factors that affect gait selection, such as quadrupedal walking speed, substrate diameter and orientation, and phylogeny. They found that phylogeny had a more substantial impact on the footfall sequence than substrate diameter (lack of influence) and orientation (relatively weak influence) through their logistic regression analysis, which used the footfall sequence (LS or DS) as the response variable and the independent factors.…”
Section: Discussionmentioning
confidence: 99%